Pengaruh Intelegence Quotient, Minat, komunikasi orang tua, dan teman sebaya terhadap keputusan siswa di SMA N 1 sungai rumbai - riko Saputra (STKIP PGRI Sumatera Barat, 2021)
ABSTRACTThe study found that: First, intelligence (IQ) (X1) has a significant effect on students' decisions to choose majors with a regression coefficient of 0.496. This coefficient value is significant because the value of t count 5.792 ≥ t table 1.65622 means that intelligence (IQ) increases by one unit. then the student's decision to choose a major also increased by 0.496. Both interests (X2) have a significant effect on students' decisions to choose majors with a regression coefficient of 0.367. This coefficient value is significant because the value of t count 10,533 ≥ t table 1.66571 means that if the interest increases by one unit. then the student's decision to choose a major also increased by 0.367. The third parent communication (X3) has a significant effect on student learning outcomes at SMAN 1 Sungai Rumbai with a regression coefficient of 0.309. This coefficient value is significant because the t value is 5.446 ≥ t table 1.65622, meaning that parental communication increases by one unit. it will increase the student's decision to choose a major by 1.073. The four peers (X4) have a significant effect on the student's decision to choose a major with a regression coefficient of 0.309. This coefficient value is significant because the t value is 4.300 ≥ t table 1.65622, it means that if peers increase by one unit. it will increase the student's decision to choose a major by 0.309. The five Intelligence (IQ), Interests, Parents Communication, and Peers simultaneously have a significant influence on students' decisions to choose majors at SMAN 1 Sungai Rumbai with Fcount 51.641 ≥ Ftable 2.28 and significant 0.000 <0.05. It is recommended that teachers, schools and parents pay more attention to or control student learning activities at school and at home so that students do not make the wrong decision to continue the educational process Keywords: Intelegence, Interest, Communication, Schoolmate, Decision